A wearable active-type X-ray dosimeter having novel functions to derive both incident direction and absolute exposure dose. (July 2023) - Asahara, Takashi; Hayashi, Hiroaki; Maeda, Tatsuya; Goto, Sota; Kobayashi, Daiki; Nishigami, Rina; Lee, Cheonghae; Ando, Miku; Kanazawa, Yuki; Imajo, Satoshi; Yamashita, Kazuta; Higashino, Kosaku
Abstract: Currently, interventional radiology (IVR) procedures using X-ray fluoroscopic equipment are widely used to perform medical diagnosis and treatment, and during these procedures medical staff are often exposed to scattered X-rays. This study aims to propose a concept of a novel dosimetric system that can analyze both the X-ray incident angle and radiation exposure dose simultaneously. Our dosimeter consists of three active-type detectors. Absolute dose rates can be determined by the center detector, and the side detectors can derive incident direction. Incident windows of the side detectors have symmetrically-sloped titanium filters to enlarge the angular dependence. These filters create a difference in the responses measured by the left and right detectors when X-rays are incident to a centered position; from this, the incident angle of the X-rays can be calculated. To verify the concept, basic experiments using a clinical fluoroscopic system were performed. It was found that our dosimeter can derive the incident angle of X-rays between ± 50° and determine the absolute dose with proper angular dependence correction. Furthermore, a fluoroscopic procedure was mimicked using a human body phantom and a mannequin on which our dosimeter with a wearable optical camera was placed. Although commercial dosimeters can determine exposure doses with a systematic uncertainty of ± 13.4%, our dosimetric system can analyze absolute exposure doses with a systematic uncertainty of ± 4.2%. Highlights: We propose a novel idea using active-type dosimeter for IVR operator. Our dosimeter can derive both the incident direction and exposure dose of X-rays. By calculating the incident angle, the angular dependence is properly corrected. The information obtained by our dosimeter is valuable for the education of the staff.